Evaluation of Factors Affecting Outcome in Growth Hormone–Secreting Pituitary Adenomas - Padwal, Amit; Gangadharan, Jagath Lal; Srinivas, Dwarakanath; Somanna, Sampath (Indian Journal of Neurosurgery, 2017)
Introduction Management of functioning pituitary adenomas is challenging as they can present with features of an intracranial mass, systemic effects, or a combination of both. In this series, one of the largest in available literature from our country, we have analyzed our experience with surgical management of growth hormone (GH)-secreting pituitary adenomas and factors influencing their hormonal remission.Materials and Methods The data of all functional pituitary adenomas operated at our institute from January 2002 to December 2011 were obtained from the case files of these patients. This was studied for various clinical-radiologic features, management stratagems, and clinical and hormonal outcomes.Results Ninety-three patients of GH-secreting pituitary adenomas with a mean age of 32.7 years were included in the study. Fifty-three (57%) patients had headache at presentation; 46 (49%) had visual complaints, whereas menstrual irregularity was seen in majority of females. Mean GH level was 52.05 ng/mL. Fifty (53%) patients had invasive adenoma; 32 had cavernous sinus extension. Among 80 patients with hormonal follow-up, 43 (53.75%) achieved remission of GH level < 5 ng/mL.Conclusion In this series, one of the largest of its kind, the main factors influencing unfavorable outcome include macroadenomas, invasiveness, high basal GH > 45 ng/mL levels, and mixed adenomas.
Keywords: pituitary adenomas; invasive adenoma; growth hormone–secreting adenomas; acromegaly